Deformation Behavior, Fatigue and Fracture Surface Microstructure of Porous Titanium Nickelide - Marchenko, Ekaterina; Yasenchuk, Yuriy; Avdeeva, Diana; Baigonakova, Gulsharat; Gunther, Sergey; Iuzhakova, Mariya (Micro and Nanosystems, 2021)
Background: The porous SHS–TiNi alloy is a widely used material for repairing defects in bone tissues. Objective: The objective of the study is to comprehensively investigate porous SHS–TiNi alloy samples for fatigue strength under cyclic bending, to study deformation characteristics under quasistatic tension and bending, and to carry out the fractographic analysis of fracture features. Methods: The study employed the electrospark method for cutting plates from a porous isotropic SHS– TiNi rod 30 mm in diameter and 300 mm in length. Results: Deformation behaviour under tension and three-point bending of porous plates showed that porous samples undergo viscoelastic deformation due to the austenite–martensite (A→M) phase transformation. The fracture surfaces of elastic porous samples were studied by SEM. Microscopic studies of fracture surfaces revealed zones of quasi-brittle fracture of martensite and viscous fracture of austenite. The porous framework of intermetallic alloy exhibits a continuous brittle layer and numerous brittle non-metallic inclusions. However, successful fatigue tests showed that brittle phases and inclusions do not significantly affect deformation and fatigue characteristics of porous titanium nickelide. It was found that 70% of porous samples sustain 106 cycles of deformation without fracture due to reversible A→M→A phase transformations in the TiNi phase, which is one of the components of multiphase porous alloy. Conclusion: Viscoelastic behavior of the porous sample and its high fatigue strength under cyclic loading is due to reversible deformation of the TiNi phase. The corrosion-resistant layer of the porous framework allows an effective use of SHS–TiNi.
Keywords: TiNi